The Civil War in Ukraine: International Law and Criminal Responsibility of Individuals for International Crimes - Ivan I. Kotlyarov; Yuliya V. Puzyreva (Московский журнал международного права, 2014)
The article presents a brief analysis of the events taking place in Ukraine in recent months; with the objectives justify their qualiﬁ cation as an armed conﬂ ict, accompanied by war crimes and gross human rights violations by the military units of Ukraine.